Retrieval of Migrated Guidewire Extending From Right Ventricular Apex to the Inferior Vena Cava via Pigtail-Assisted Snaring - Jarallah Yaseen, Manaf; Nori, Wassan; K Shukur Al-Ghanimi, Mohanad (Scripta Medica, 2026)
Intravascular embolisation of foreign bodies (FB) is a rare, serious complication that may occur during central venous line insertion. A 39-year-old male in a critical condition presented to casualty department with a through-and-through chest gunshot wound. Chest X-ray showed left haemothorax; an urgent chest tube was introduced and central venous access was introduced via the right femoral vein. The guided wire used in the procedure was unintentionally pushed to reach the right ventricular apex. Echocardiography confirmed FB location. Once stabilised, the patient was referred to Iraqi Centre of Cardiac Diseases, where transcatheter retrieval was performed. To stabilise the FB, a 6F pigtail catheter was used to create a U-shaped loop in the guided wire body, coupled with successful snaring. By strategic planning and effective teamwork, retrieval of FB was safely accomplished using a standard catheterisation tool from a high-risk anatomical site without complication.